The Potential Protective Effect of Iridoid Glycosides Isolated From Osmanthus fragrans Seeds Against the Development of Immune Liver Injury in Mice - Zhang, Yuchen; Xiao, Feng; Zhou, Qiqi; Diao, Tingting; Zhang, Meng; Liu, Dongyang; Wang, Zhuowen; Huang, Ting; Wu, Yupei; Bai, Yuting; Min, Qing (Frontiers in Pharmacology, 2021)
Objective: The iridoid glycosides were extracted and separated from Osmanthus fragrans seeds and the potential protective effect of Osmanthus fragrans seed extract on concanavalin A-induced immune liver injury in mice was studied. Methods: Osmanthus fragrans seeds were extracted by 95% ethanol reflux. Then, the iridoid glycosides were enriched by extraction refined through petroleum ether(60-90 ℃), ethyl acetate, and water-saturated of n-butanol in sequence, so as to purify the n-butanol part(Osmanthus fragrans seed’s n-butanol extraction, OFSN) by macroporous resin. Specnuezhenide and Nuezhennoside G13 were used as the reference substance to determine the concentration of iridoid glycosides by HPLC. On this basis, mice immune liver injury model was established by tail intravenous concanavalin A (20 mg/kg); the content of serum ALT, AST, IFN-γ, TNF-α, and the content of liver tissue MDA, SOD was determined; the pathological changes of the liver by HE staining were observed; the expression levels of p38MAPK and p-p38mapk in liver tissue were detected by WB. Results: The linear, precision, repeatability, recovery and stability of HPLC are all met the requirements by validated with methodology. The content of Specnuezhenide and Nuezhenoside G13 in the n-butanol extracts were 39.20% and 39.88%, respectively. Actually, their content can reach up to 82.56% and 87.9% after being purified by macroporous resin. The results of animal experiments show that OFSN could significantly reduce the liver and spleen index, reduce the ALT and AST content in plasma, and the MDA content in liver tissue, and then increase the SOD content. Besides, OFSN could also reduce the plasma IFN-γ, TNF-α level. HE staining result indicates that the pathological changes in the liver tissues of mice treated with OFSN are alleviated to different degrees while WB result suggests that OFSN could significantly inhibit the expression of p-p38mapk. Conclusion: Osmanthus fragrans seeds are rich in iridoid glycosides, which has a good protective effect on mice immune liver injury caused by concanavalin A. The mechanism may be related to inhibiting the phosphorylation of p38MAPK, inhibiting the release of inflammatory mediators, improving the antioxidant capacity of liver cells, and weakening the occurrence of lipid peroxidation.